OMANI STUDENTS’ PERCEPTIONS OF THE IMPACT OF PRIVATE TUTORING ON ACADEMIC PERFORMANCE - Al Hunaini , Hamood Ahmed; Al Hajri , Rashid Mohammed; Chinnathambi , Kodhandaraman (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
Private tutoring is becoming increasingly common worldwide as a way to supplement formal education, especially in developing countries. This growing trend has attracted significant attention from researchers who are using various methods to understand the reasons behind the demand for private tutoring and its Impact on students, focusing on key variables such as gender, grade level, and the relationship between tutoring participation and test scores. However, few research studies examine how Omani students perceive the Impact of private tutoring on their academic performance. Therefore, this study aims to investigate Omani students’ perceptions of private tutoring and its Impact on their academic performance. The study employed a quantitative research method and collected data from 1,111 Omani students studying in grades 9 to 12 (high and higher secondary schools) by distributing a self-prepared questionnaire. The data were analyzed in SPSS using descriptive and regression analysis to determine the factors influencing the test scores. The multiple regression analyses indicate a positive correlation between private tutoring and Omani students’ academic achievement (F = 5.210, p = 0.006). However, receiving private tutoring (p = 0.543) is not statistically significant, whereas the number of days attended is statistically significant (p = 0.001). Overall, the study’s findings reveal that mere participation in private tutoring does not have a positive effect on test scores, but regularly attending private tutoring is positively associated with test scores. The study recommends consistent engagement with private tutoring to improve students’ academic performance. The study also provides significant implications for teachers, parents, and policymakers. JEL Classification Codes: I21, D12, O15.